2010
DOI: 10.1111/j.1759-7714.2010.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P38 MAPK on the apoptosis of human lung adenocarcinoma cell induced by the spider venom

Abstract: Background: The venom of spiders may inspire new drugs to treat carcinoma. The aim of this study was to investigate the effect of P38 MAPK on tumor necrosis factorrelated apoptosis of lung adenocarcinoma cell line by spider venom. Methods: Lung adenocarcinoma A549 cells were cultured in PRMI-1640 medium and the apoptosis rate was observed after treatment with spider venom with a flow cytometer. The expression of P38 MAPK protein in lung cancer cells was analyzed using Western blot. Results: After targeting spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Our results show that a 24 hours treatment of PC3 cells with the IC 50 of these venoms caused a significant increase in the activity of the antioxidant enzymes in the cell lysate compared to the control cells (Table 1). This agrees with reports that showed an increase in lipid peroxidation level and antioxidant enzymes when using venom as a treatment 28,29. In addition, da Silva et al7 reported increased activities of CAT and GST in venom-injected experimental animals, which also agrees with our results.…”
Section: Resultssupporting
confidence: 93%
“…Our results show that a 24 hours treatment of PC3 cells with the IC 50 of these venoms caused a significant increase in the activity of the antioxidant enzymes in the cell lysate compared to the control cells (Table 1). This agrees with reports that showed an increase in lipid peroxidation level and antioxidant enzymes when using venom as a treatment 28,29. In addition, da Silva et al7 reported increased activities of CAT and GST in venom-injected experimental animals, which also agrees with our results.…”
Section: Resultssupporting
confidence: 93%
“…Apoptosis, necrosis, and lysis of tumor cells are possible mechanisms by which the drug inhibited tumor growth. In vitro and in vivo assays on human cervical carcinoma cell line (HeLa), 15 hepatocellular carcinoma cell line (BEL-7402), 16 and human lung adenocarcinoma 17 suggested that SV facilitates apoptosis and functions as an effective anticancer agent. Further, more structural aspects responsible for these activities need to be defined, and the results of more advanced in vivo tests will be pivotal in contemplating SVs further development as a clinically useful pharmaceutical agent.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were washed with PBS and 50(L of sodium 3’-[1-phenylamino-carbonyl)-3,4-tetrazolium]-bis (4-methoxy-6-nitro) benzene-sulfonic acid hydrate (MTT) at 1 mg/mL concentration was added to each well. The cells were incubated for 4 hours before the addition of 100 µL dimethyl sulfoxide and absorbance was read at 570nm using Multiskan GO Microplate Spectrophotometer (Thermo Scientific, USA) [ 9 ]. Average triplicate readings and blanks were utilized to determine the inhibition rate.…”
Section: Methodsmentioning
confidence: 99%